Frequency Nesting Interactions in the Subthalamic Nucleus Correlate With the Step Phases for Parkinson’s Disease - Jin, Luyao; Shi, Wenbin; Zhang, Chuting; Yeh, Chien-Hung (Frontiers in Physiology, 2022)
Gait disturbance in Parkinson’s disease (PD) can be ameliorated by sound stimulation. Given the excessive β synchronization in basal ganglia is linked to motor impairment in PD, whether the frequency nesting interactions are associated with the gait problem is far from clear. To this end, the masking phase-amplitude coupling (PAC) method was proposed to overcome the trade-off between intrinsic nonlinearity/non-stationarity and demand for predetermined frequencies, normally extracted by the filter. In this study, we analyzed LFPs recorded from 13 patients (one female) with PD during stepping with bilateral deep brain electrodes implanted in the subthalamic nucleus (STN). We found that not only high-frequency oscillation (100-300 Hz) was modulated by β (13-30 Hz), but β and γ amplitude were modulated by their lower-frequency components in δ/θ/α and δ/θ/α/β bands. These PACs were suppressed by sound stimulation, along with an improvement in gait. We also showed that gait-related high-β (Hβ) modulation in STN was sensitive to auditory cues, and Hβ gait-phase modulation increased with a metronome. Meanwhile, phase-locking values (PLVs) across all frequencies were significantly suppressed around contralateral heel strikes, manifesting the contralateral step as a critical gait phase in gait initiation for PD. Only the PLVs around contralateral steps were sensitive to auditory cues. Our results support the masking-PAC as an effective method in exploring frequency nesting interactions in LFPs, and reveal the linkages between sound stimulation to multiple coupling measures in STN per se or to the gait-phases for PD during stepping. These findings raise the possibility that nesting interactions in STN work as feasible biomarkers in alleviating gait disorders.